Non-invasive femoropopliteal assessment: is that angiogram really necessary?. Issue 6554 (25th October 1986) - Shearman, C P; Gwynn, B R; Curran, F; Gannon, M X; Simms, M H
Abstract : A method of non-invasive preoperative assessment of chronically ischaemic legs was developed that used clinical data and data derived from Doppler ultrasonography to produce a numerical score that could be compared with an angiographic score for stenosis of the popliteal artery trifurcation. The two scoring systems were applied retrospectively to 144 legs after femorodistal bypass. A close correlation was observed (r = 0.89, p less than 0.001), and both systems tended to predict the level of grafting undertaken. A prospective comparison was then made in 81 ischaemic legs that were examined by arteriography; the correlation between the two scoring systems remained close (r = 0.89, p less than 0.001), and the level of bypass was correctly predicted by the non-invasive assessment in 44 of 50 legs that were operated on. Use of the non-invasive assessment subsequently greatly reduced the indications for preoperative arteriography in patients requiring femorodistal vascular reconstruction.